2022
DOI: 10.1177/09544089221109835
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the grinding process utilizing an auxiliary compressed air jet on cleaning the grinding wheel surface

Abstract: Grinding is one of the most complex and precise machining operations, with the performance of the grinding wheel being heavily reliant on its surface conditions. Removed chips tend to be forced back to the wheel surface due to the intense heat generated in the grinding zone. The loaded chips block the wheel's grinding capability, resulting in increased grinding force and temperature, wheel chatter, and workpiece thermal degradation. To solve these problems, this research examines the effectiveness of an auxili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Therefore, specific grinding energy falls [ 66 ]. Similar to roughness, when the nozzle angle is 45, an optimum value of specific grinding energy is obtained due to better cleaning and cooling and lower grinding zone temperature [ 7 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, specific grinding energy falls [ 66 ]. Similar to roughness, when the nozzle angle is 45, an optimum value of specific grinding energy is obtained due to better cleaning and cooling and lower grinding zone temperature [ 7 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the following, Hatami Farzaneh et al used an auxiliary compressed air jet system to investigate the effect of the incidence angle at various angles to clean the wheel surface and reduce wheel loading. The results showed that an incidence angle of 45 de grees produced the best results in terms of surface roughness, diametrical grinding wheel wear, G -ratio, tangential forces, specifi;c energy, and wheel loading analysis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang [91] , Wang [85] 和 Wang [92] 等在砂带磨削过程中基 于砂带图像分析和分类提升算法, 对砂带的磨损类 型进行识别和分析. Farzaneh [93] 等采用计算机图像处 [94] ,…”
Section: F O R R E V I E W O N L Yunclassified
“…Intense fluid jetting is a key technical element in a number of industrial devices, e.g., grinding [1][2][3], cutting [4,5], etc. The detailed characterization of multiphase gas-liquid flows is critical in metallurgical processes, the design of efficient air and ground devices, combustion devices in aircraft and aerospace systems, and engines in transportation and marine engines, as well as when developing new technologies leading to technological advances [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%